PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK MENENTUKAN JURUSAN YANG TEPAT BAGI SISWA MADRASAH ALIYAH NEGERI - Satria; Wirawan, Abie; Husin, Ishak; Ilham Ramdhani, Adhitya; Sulistyowati, HS; Mutaqin Subekti, Zaenal (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
One in the field of services and services. Make-up services exist to meet the make- up needs of various events, helping women to be more confident and special on their special days. In Bekasi, there is one facial makeup artist who offers her services, namely Syifa Beauty. However, in terms of marketing, this service still uses manual methods, so promotions and information obtained by potential customers are limited. The information system for make-up service providers is designed as a meeting medium for make-up service providers and potential customers with the help of technology. The purpose of this system is to facilitate Make-Up service providers in carrying out promotions and to reduce promotional costs. The system will display examples of service results, prices, and group them into several categories so that potential customers will be free to explore and determine the services they will order. Therefore, a system was developed that can assist the ordering process for customers and provide information on the services provided by Syifa Beauty. The method used in this research was observation and interviews. The system development method used is Rapid Application Development (RAD) using the PHP programming language and Mysql and UML databases as the design process. This research produces a system that can order makeup services via the website and can see what services are provided and the prices of each makeup service available at Syifa Beauty